How to bend galaxy disc profiles: II. stars surfing the bar in Type-III discs - Herpich, Jakob; Stinson, G. S.; Rix, Hans-Walter; Martig, M.; Dutton, Aaron A. (Monthly notices of the Royal Astronomical Society, 2017)
The radial profiles of stars in disc galaxies are observed to be either purely exponential (Type-I), truncated (Type-II) or antitruncated (Type-III) exponentials. Controlled formation simulations of isolated galaxies can reproduce all of these profile types by varying a single parameter, the initial halo spin. In this paper, we examine these simulations in more detail in an effort to identify the physical mechanism that leads to the formation of Type-III profiles. The stars in the antitruncated outskirts of such discs are now on eccentric orbits, but were born on near-circular orbits at much smaller radii. We show that, and explain how, they were driven to the outskirts via non-linear interactions with a strong and long-lived central bar, which greatly boosted their semimajor axis but also their eccentricity. While bars have been known to cause radial heating and outward migration to stellar orbits, we link this effect to the formation of Type-III profiles. This predicts that the antitruncated parts of galaxies have unusual kinematics for disc-like stellar configurations: high radial velocity dispersions and slow net rotation. Whether such discs exist in nature, can be tested by future observations.